Geo Information Technologies as a Tool for Managing Tourism Resources - Tigran Babayan (Indonesian Journal of Law and Economics Review, 2020)
Today, the process of developing tourist destinations is possible only by using modern spatial planning tools for tourism market entities. To carry out this in the power of geographic information technologies, which are actively being implemented in all spheres of our life, including in tourism. For a real assessment of the recreational potential of the region, which has unique natural, historical and cultural potential, it is necessary to create geographic information systems (GIS), which reflect in the same way all the rest necessary for implementation in tourism products, infrastructure. Simple sites of travel agencies, service sectors, paper maps, guides and other well-known materials are not capable of flexibility and, most importantly, quickly respond to changes, innovations. These factors are especially valuable when studying the potential of the territory, for the compilation of tourism products of different levels of service. This approach can guarantee the development of tourism in any territory. Moreover, make a forecast for long-term targeted programs in the development of tourism. Geo information technologies are able to not only generate demand, but also indicate investment vectors for territorial development in order to turn it into a tourist destination. The article considers the issues of geographic information support in the goals of tourism development using the example of a small mountainous regions of the Republic of Armenia. The experience of certification of resources for tourism is considered.